STUDY ON IN VITRO DISSOLUTION OF CALCIUM OXALATE RENAL STONE BY SHILAJIT - Ahmad, Shafiq; Ansari, Tariq Mahmood; Shad, Muhammad Aslam (Indonesian Urological Association, 2020)
Objective: This study aims to test the solubility efficiency of Shilajit in vitro for calcium oxalate renal stone. Material & Methods: A small stone was selected for the experiment. The weighed stone was suspended in 25 ml of aqueous extract of Shilajit for 72 hours with the interval of 24 hours. After each 24 hours, the stone was taken out, washed, dried and difference in weight was calculated. The whole procedure was carried out at room temperature. Results: It was found that the weight of the stone was reduced. Conclusion: Shilajit has the ability to dissolve the calcium oxalate renal stone.